A Comparative Investigation on Different QoS Mechanisms in Multi-Homed Networks - Haider W. Oleiwi; Heba L. Al-Taie; Nagham Saeed; Doaa N. Mhawi (Iraqi Journal of Industrial Research)
The current wireless communication system in Iraq faces several challenges during users’ handoff, especially with the fast growth of users and demands. This is also a global issue; therefore, quality of service (QoS) measures have rapidly become more important and developed over the years. The complexity of communication between diverse applications and underlying QoS architectures leads to these deployment problems, which decreases the utility of QoS provisioning. This paper studies different QoS aggregation mechanisms in order to improve the overall operational efficiency of the multi-homed node. The main QoS mechanisms, i.e., IntServ, DiffServ, best-effort, and IntServ-DiffServ were investigated and compared thoroughly. Furthermore, it focuses on the multi-homed network that aims to develop a scalable system with better performance, reliability, and optimized communication networks. In this paper, multi-homed network enhancements are carried out with the comparable site and host multi-homing. The results show how the IntServ-DiffServ has achieved the best overall performance compared to the other mechanisms as it combines the advantages of the IntServ and DiffServ mechanisms. Another important finding was that the multi-homing managed to keep the communication going on the multi-homed node, whereas the site-multi-homing gave a better overall end-to-end latency over the host-multi-homing.